IMPELEMENTASI METODE CARD SHORT UNTUK MENINGKATKAN HAFALAN AL-QUR’AN HADITS PADA SISWA KELAS III MDTA NURUL HUDA DESA SUNGAI KUNING KECAMATAN SINGINGI - Dina Masdalova (Universitas Islam Kuantan Singingi, 2020)
This study aims to find out how the implementation of the card short method in improving the memorization of students in MDTA Nurul Huda Singingi District,Kuantan Singingi District. This research is Classroom Action Research with research stages, namely Pre Cycle, Cycle I and Cycle II, the test is a primary data collection method. The results showed that. The results on Pre-Cycle are known to students whoare able to memorize the surah studied has a percentage of 70%, in Cycle I also obtained a percentage of 70% but with an increasing number of values, in Cycle II, the student's memorization data rose to 100%. On this basis, it is known that the use of the Card Short method in learning the Qur'an in the Hadith at MDTA Nurul Huda Sungai Kuning Village Singingi District Kuantan Singingi Regency is able to increase the memorization of students.